"A Community of Peoples" : Studies on Society and Politics in the Bible and Ancient Near East in Honor of Daniel E. Fleming - Monroe, Lauren A.S.; Stahl, Michael J.; Johnson, Dylan R.; Leonard-Fleckman, Mahri (Harvard Semitic Studies., 2022)
A "Community of Peoples": Studies on Society and Politics in the Bible and Ancient Near East in Honor of Daniel E. Fleming draws together a diverse community of scholars to honor the career of Daniel E. Fleming as a historian of the Bible and ancient Near East. Together, these scholars participate in a dynamic historical enterprise, each one positioning themself along a Middle Eastern spatial-temporal continuum stretching from the Old Babylonian to the Persian periods. Each contributor attempts to touch a sliver of ancient history, whether a particular person or community, a text or visual image or scribal process. They do so through a diversity of methods and disciplines, which together reflect the possibilities and promises for history writing. The Harvard Semitic Studies series publishes volumes from the Harvard Semitic Museum. Other series offered by Brill that publish volumes from the Museum include Studies in the Archaeology and History of the Levant and Harvard Semitic Monographs , https://semiticmuseum.fas.harvard.edu/publications .